Mucosa-Colonizing Microbiota Correlate With Host Autophagy Signaling in Patients With Inflammatory Bowel Disease - Wang, Wenxue; Liu, Zhongjian; Yue, Wei; Zhu, Ling; Zhong, Huijie; Yang, Chao; He, Tian; Wan, Ping; Geng, Jiawei (Frontiers in Microbiology, 2022)
Both bacteria and autophagy are implicated in inflammatory bowel disease (IBD) pathogenesis. However, how bacteria crosstalk with autophagy signaling remains largely known, especially in intestinal mucosa. This study aimed to profile the internal complex autophagy signaling cascade and their external correlation with these bacteria, and consequently provide a systematic and precise target for future IBD diagnosis and therapy. We found the UC patients exhibited more severe dysbiosis than the CD patients, as represented by alpha diversity, community phenotypes, and functional annotation compared with the control population. Meanwhile, CD patients showed greater transcriptional signaling activities of autophagy, endoplasmic reticulum (ER) stress, and bile acid production. Dominant bacteria (e.g., Rhodococcus, Escherichia, Shigella, and Enterococcus) were positively correlated and low-abundance bacteria (e.g., Bacillus, Acidovorax, Acinetobacter, and Stenotrophomonas) were negatively correlated with the autophagy signaling cascade (184 autophagy genes, 52 ER stress genes, and 22 bile acid production genes). Our observations suggested UC patients showed temporary and widespread microbiota turbulence and CD patients showed processive and local autophagy activity during IBD progression. Intestinal mucosa-colonizing bacteria were correlated with the bile/ER stress/autophagy signaling axis in IBD pathogenesis.